A closer look at the natural history and recurrence patterns of high-grade truncal/extremity leiomyosarcomas: A multi-institutional analysis from the US Sarcoma Collaborative. (September 2020) - Lee, Rachel M.; Ethun, Cecilia G.; Zaidi, Mohammad Y.; Tran, Thuy B.; Poultsides, George A.; Grignol, Valerie P.; Howard, John H.; Bedi, Meena; Gamblin, T. Clark; Tseng, Jennifer; Roggin, Kevin K.; Chouliaras, Konstantinos; et al.
Abstract: Background/objective: Natural history and outcomes for truncal/extremity (TE) soft tissue sarcoma (STS) is derived primarily from studies investigating all histiotypes as one homogenous cohort. We aimed to define the recurrence rate (RR), recurrence patterns, and response to radiation of TE leiomyosarcomas (LMS). Methods: Patients from the US Sarcoma Collaborative database with primary, high-grade TE STS were identified. Patients were grouped into LMS or other histology (non-LMS). Primary endpoints were locoregional recurrence-free survival (LR-RFS), distant-RFS (D-RFS), and disease specific survival (DSS). Results: Of 1215 patients, 93 had LMS and 1122 non-LMS. In LMS patients, median age was 63 and median tumor size was 6 cm. In non-LMS patients, median age was 58 and median tumor size was 8 cm. In LMS patients, overall RR was 42% with 15% LR-RR and 29% D-RR. The 3yr LR-RFS, D-RFS, and DSS were 84%, 65%, and 76%, respectively. When considering high-risk (>5 cm and high-grade, n = 49) LMS patients, the overall RR was 45% with 12% LR-RR and 35% D-RR. 61% received radiation. The 3yr LR-RFS (78vs93%, p = 0.39), D-RFS (53vs63%, p = 0.27), and DSS (67vs91%, p = 0.17) were similar in those who did and did not receive radiation. High-risk, non-LMS patients had a similar overall RR of 42% with 15% LR-RR and 30% D-RR. 60% of non-LMS patients received radiation. There was an improved 3yr LR-RFS (82vs75%, p = 0.030) and DSS (77vs65%, p = 0.007) in non-LMS patients who received radiation. Conclusions: In our cohort, patients with LMS have a low local recurrence rate (12–15%) and modest distant recurrence rate (29–35%). However, LMS patients had no improvement in local control or long-term outcomes with radiation. The value of radiation in these patients merits further investigation. Highlights: High risk soft tissue sarcomas are defined as high grade and >5 cm in size. Standard of care is multi-modality therapy with surgery and radiation. Leiomyosarcomas may have more aggressive biology than other histological subtypes. Radiation may not have a benefit for Leiomyosarcomas. Prospective studies are needed to investigate this finding.